Pattern and prevalence of neonatal thrombocytopenia in Port Harcourt, Nigeria - Zaccheaus A Jeremiah; Justina E Oburu (Dove Medical Press, 2010)
Zaccheaus A Jeremiah1, Justina E Oburu21Hematology and Blood Transfusion Science Unit, Department of Medical Laboratory Sciences, College of Health Sciences, Niger Delta University, Wilberforce Island, Bayelsa State, Nigeria; 2Department of Hematology and Blood Transfusion University of Port Harcourt Teaching Hospital, Port Harcourt, NigeriaBackground: In Port Harcourt, evidence-based guidelines for platelet transfusion therapy in neonatal patients are yet to be defined and the prevalence and pattern of neonatal thrombocytopenia has not yet been reported.Methods: Platelet counts of 132 neonatal patients admitted into the special care baby unit (SCBU) at the University of Port Harcourt Teaching Hospital in Nigeria were assessed using the International Committee on Standards in Hematology (ICSH) approved manual procedures for hemocytometry.6Study design: This is a cross sectional study carried out on neonates to determine the prevalence and pattern of neonatal thrombocytopenia.Results: The median platelet count of the neonates was 97.0 × 109/L (interquartile range [IQR] 50–152) while the mean age was 61.7 hours (range 1–336 hours). The overall prevalence of neonatal thrombocytopenia was 53.0%. Mild thrombocytopenia (platelet count 51–100 × 109/L) was found in 39.4% of the neonates, 12.1% had moderate thrombocytopenia (platelet count 30–50 × 109/L), while severe thrombocytopenia (platelet count <30 × 109/L) was detected in 1.5% of the neonates. Of these, 84.84% of the cases occurred within 72 hours (early onset). The most common clinical diagnosis among the neonates was severe birth asphyxia (33.3%), followed by neonatal jaundice (19.7%), neonatal sepsis (16.7%), low birth weight (13.6%), anemia and bleeding (6.1%), and other clinical conditions (10.6%). There was no association between clinical diagnosis and thrombocytopenia (Fisher’s exact test = 10.643; P = 0.923).Conclusion: There is a high prevalence of early onset neonatal thrombocytopenia cases in this region of Nigeria, the majority of which are mild in nature. There is a need to define a safer lower limit for platelet count and to determine which neonates will benefit from treatment.Keywords: neonatal thrombocytopenia, platelet count, thrombocytopenia, Port Harcourt, Nigeria